Employer branding, organization’s image and reputation, and intention to apply: the moderating role of the availability of organizational information on social media - Thang, Nguyen Ngoc; Trang, Pham Thu (Frontiers in Sociology, 2024)
The topics of employer branding and organization's image and reputation have been well-researched in the literature. However, most empirical studies were conducted in Europe, Australia, or the United States, but very few were conducted in Asia, especially in Vietnam. In addition, the interaction of image and reputation with the availability of information on social media is poorly understood. Using signaling theory for building a research model, we collected data from 206 Generation Z respondents from the logistics sector in Vietnam. Our findings show that (i) employer branding has positively and significantly related to an organization's image and reputation; (ii) the organization's image and reputation had a significant effect on job seekers' intention to apply; and (iii) the interaction of image and reputation with availability of information on social media to predict the job seeker's intention to apply. The paper also presented implications for both researchers and practitioners as well as recommendations for future research.